What is the future for Central Asian endorheic lakes? A water balance model for Shortandy Lake, Burabay National Nature Park, Kazakhstan - Baigaliyeva, Marzhan (2021)
Lakes are recognised as having a high sensitivity to environmental change and human interventions. This is particularly the case with endorheic lakes due to the fact that their water volume is not controlled by outflow from a river outlet. Most of the endorheic lakes are formed in dry, i.e. in arid or/and semi-arid regions. Central Asia occupies one-third of the arid area of the world, where lakes are a valuable source of freshwater for irrigation and daily usage. This thesis investigates the reasons for the lake volume decline in Shortandy Lake; one of the endorheic lakes located in Burabay National Nature Park (BNNP) in Northern Kazakhstan. BNNP was established in order to preserve and restore the unique landscape of the region, which plays an important role in ecologic, scientific and recreational dimensions. The Park consists of a number of endorheic lakes, in which water volumes have been fluctuating during the last century. However, the reasons for the current trends in water volume reduction in the Burabay lakes system remain unexplored. This PhD project develops and validates a new water balance model for Shortandy Lake that is built from fundamental hydrological relationships. The water level and volume of the lake is estimated monthly using estimates of daily open water and grass evaporation, snowmelt and rainfall-induced runoff from observed climate variables available from the State Hydro-meteorological agency. Crucially, it also incorporates estimates of anthropogenic water abstraction. The water balance model is applied to assess future water volume changes under changing future climate scenarios. The analysis reveals new information on the potential impacts of regional climate fluctuation as well as allowing assessment of the impact of past and future water management strategies in the Shortandy Lake catchment.